Legal Instrument Under the “ASEAN Way”: The Case of ASEAN Convention Against Trafficking in Persons - Wirawan, Made; Novikrisna, Dian (UI Scholars Hub, 2024)
This study was mainly raised because of the contradictory situation between ASEAN’s informal practices, embodied in the ASEAN Way, and the emergence of the ASEAN Convention against Trafficking in Persons (ACTIP) as a legal instrument for the basis of formal cooperation. Hence, it is important to understand the current situation of the ASEAN Way on a legal instrument by examining how ACTIP conforms with the ASEAN Way principles and influences its compliance. Drawing on the concept of legalization as discussed by Abbott et al. (2000), the research employs a qualitative method and a case study approach to analyze ACTIP’s provisions and their alignment with the ASEAN Way. The findings reveal that ACTIP’s conformity with the ASEAN Way positions it as a soft law. However, this allows member states to achieve ACTIP’s goals while managing uncertainties and preserving their sovereignty. Significantly, this study highlights the adaptation of the ASEAN Way in a legal instrument that uniquely poses no significant problems and instead works to suppress the tradeoffs of international law.